Blast off! : how Mary Sherman Morgan fueled America into space - Slade, Suzanne (Calkins Creek, an imprint of Astra Books for Young Readers, 2022)
Chronicles the life of the first female rocket scientist who, chosen to create the fuel to launch a rocket carrying America's first satellite, broke gender barriers and overcame many challenges to succeed.